2007
DOI: 10.1666/06-022r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Hexactinellid and associated sponges from the upper Reef Trail Member of the Bell Canyon Formation, southern Guadalupe Mountains National Park, Texas

Abstract: A small faunule of silicified hexactinellid sponges and root tufts has been recovered from the upper Guadalupian Reef Trail Member of the Bell Canyon Formation, from the Patterson Hills, in the southwestern part of the Guadalupe Mountains National Park in western Texas. Some demosponges from the type section of the Reef Trail Member, near the mouth of McKittrick Canyon on the front of the Guadalupe Mountains in the park, have also been documented. Included in the faunule from the Patterson Hills localities are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Finks & Rigby (2004) included several families of Palaeozoic hexactinellids, including Ordovician forms, in the Amphidiscophora, based on the presence of lyssacine skeletons which have no fusion of spicules in any part of the body. Although the presence of amphidics or hemidisc microscleres was included in the diagnoses of the Palaeozoic Amphidiscophora, only in the Carboniferous (Kling & Reif 1969) and Permian (Rigby et al 2007) were true amphidiscs and hemidiscs found associated with megascleres.…”
Section: Discussionmentioning
confidence: 99%
“…Finks & Rigby (2004) included several families of Palaeozoic hexactinellids, including Ordovician forms, in the Amphidiscophora, based on the presence of lyssacine skeletons which have no fusion of spicules in any part of the body. Although the presence of amphidics or hemidisc microscleres was included in the diagnoses of the Palaeozoic Amphidiscophora, only in the Carboniferous (Kling & Reif 1969) and Permian (Rigby et al 2007) were true amphidiscs and hemidiscs found associated with megascleres.…”
Section: Discussionmentioning
confidence: 99%
“…Following a high Paleozoic diversity, most groups dominant in that era had disappeared by the end of the Permian (Mostler 1990;Mehl 1996;Mehl-Janussen 1999;Krautter 2002). Because the taxonomically important microscleres are rarely preserved in situ (but see, e.g., Kling andReif 1969 andRigby et al 2007 for notable exceptions), and Paleozoic skeletal architectures differ greatly from Mesozoic and modern forms (Mehl and Mostler 1993;Mehl 1996), relationships of these taxa to extant hexactinellids remain largely elusive. Thus, fossils assigned to modern families are mostly confined to the Mesozoic-Cenozoic.…”
Section: Introductionmentioning
confidence: 99%
“…Quite often, only the root tufts that were buried in the sediment during the sponges' lifetime have been preserved (Leys et al 2007). The isolated root tufts of lyssacinosids and other non-rigid hexactinellid sponges were often described from other assemblages of fossil sponges, e.g., from Eocene of Catalonia (Pisera and Busquets 2002) or Permian of Texas (Rigby et al 2007). The lack of well-preserved specimens and occurrence of dispersed spicules in the Campanian deposits result most likely from a slow rate of sedimentation and periodic weak bottom currents, which prevented the accumulation of the sediment and favored destruction of skeletons of dead sponges.…”
Section: Paleoecological Significancementioning
confidence: 99%